'But what about men?' Gender disquiet in international criminal justice. (May 2021) - Ullrich, Leila
This article explores the everyday remaking of patriarchy in international criminal justice. Drawing on 63 interviews at the International Criminal Court in The Hague and in Uganda, it argues that a gender backlash has been fomenting in international criminal justice, as practitioners express their disquiet about the 'ubiquitous gender discourse'. They claim that the Court's 'gender agenda' is in no small part driven from 'outside' and lament that it neglects the rape of men. The article traces how patriarchal norms are refashioned in international criminal justice by playing into legal sensibilities that see procedure rather than substantive change as the essence of (criminal) law. Ultimately, the article shows how attempts to foreground victims of Sexual and Gender-Based Violence in international criminal justice first failed to include men, and now, in a belated effort to rectify their omission, construct their competitive victimhood in ways that reinforce rather than challenge patriarchal norms.